Community-supported models for girls' education in Pakistan: the transformational processes of engagement. Issue 6 (17th August 2016) - Razzaq, Jamila
ABSTRACT: This article presents the case for promoting girls' education in the contexts of geographic isolation, social conservatism, fragility, and severe financial hardship, with localised services delivered through community supported initiatives, contextualised approaches, and flexible strategies. To examine the significance of using localised approaches for improving girls' access to education, the article explores three case studies from Pakistan in three different contexts. These cases highlight lessons learnt for establishing responsive and flexible girls' education initiatives which are relevant in the cultural, social, financial, and political contexts of the girls and their communities.